Total Phenolics, Flavonoids, and Anthocyanin Contents of Six Vireya Rhododendron from Indonesia and Evaluation of their Antioxidant Activities - Mohamad Rafi & , Salina Febriany, Puji Wulandari, Irma Herawati Suparto & & , Taopik Ridwan, Sri Rahayu, Dyan Meiningsasi Siswoyo (Journal of Applied Pharmaceutical Science, 2018)
Six species of Vireya Rhododendron from Indonesia, i.e. Rhododendron javanicum, R. jasminiflorum, R. konori, R. malayanum, R. retusum and R. seranicum were analyzed for total phenolics, flavonoids, anthocyanin and antioxidant activities of their ethanolic extract of leaves and twigs. Total phenolics, flavonoids and anthocyanin contents varied from 11.98–48.11 mg equivalent gallic acid/g dried powder, 0.78–8.92 mg equivalent quercetin/g dried powder and 0.12–0.29 mg equivalent cyanidin-3-glucoside/g dried powder, respectively. Antioxidant activities were investigated by using 2,2-diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and cupric ion reducing antioxidant capacity (CUPRAC). From the twig bark extracts, R. retusum has the highest antioxidant capacity by DPPH method of about 36.68 μmol trolox/g dry weight. Among the leaves extracts, R. konori has the highest antioxidant capacity of about 941.76 and 1793.62 μmol trolox/g dried powder by FRAP and CUPRAC method, respectively. From the results obtained, only total phenolics content correlated with the antioxidant measured by DPPH, FRAP, and CUPRAC. Consequently, the antioxidant activity of Vireya Rhododendron is not only attributed to the flavonoids and anthocyanin, but also from other phenolics compounds.
Keywords: Antioxidant activity, Rhododendron, anthocyanin, flavonoids, phenolics.